Attenuated positive psychotic symptoms and social anxiety: Along a psychotic continuum or different constructs?. (30th January 2016) - Cooper, Shanna; Klugman, Joshua; Heimberg, Richard G.; Anglin, Deidre M.; Ellman, Lauren M.
Abstract: Social anxiety commonly occurs across the course of schizophrenia, including in the premorbid and prodromal phases of psychotic disorders. Some have posited that social anxiety may exist on a continuum with paranoia; however, empirical data are lacking. The study aim was to determine whether attenuated positive psychotic symptoms are related to social anxiety. Young adults ( N =1378) were administered the Prodromal Questionnaire (PQ), which measures attenuated positive psychotic symptoms (APPS), and the Social Phobia Scale (SPS), which measures a subset of social anxiety symptoms. Confirmatory factor analyses were conducted to address the extent to which social anxiety and APPS tap distinct dimensions. Confirmatory factor analyses support the existence of a separate social anxiety factor scale and four separate, though interrelated, APPS factor domains (unusual thought content, paranoia/suspiciousness, disorganized thinking, and perceptual abnormalities). Additionally, social anxiety was significantly, but not differently related to each APPS domain, although the magnitude was reduced between social anxiety and distressing APPS. The current study suggests that social anxiety and attenuated positive psychotic symptoms are separable constructs, but are significantly associated with each other. Highlights: Social anxiety and attenuated positive psychotic symptoms (APPS) are associated. Social anxiety and paranoia/suspiciousness are distinct symptom clusters. Social anxiety is more related to non-distressing than distressing APPS. Social anxiety may be a consequence of or co-occur with APPS.